Approaching a postcolonial Filipino identity in the music of Lucrecia Kasilag - Tan, Arwin Q. (Musika Jornal, 2014)
This paper focuses on the lone national artist awardee of 1989, Lucrecia Kasilag. She was one of the Filipino musicians of the second half of the 20th century who searched for a distinct representation of a postcolonial national identity through her art. As many were perplexed by the unavoidable presence of western influence in the music that Filipinos have long identified themselves with, she embraced this as a natural tendency of a nation formerly subjugated by a western colonial power. In this paper, I shall examine the impact of Kasilag's contributions to nation building, as a composer, administrator, and educator, framed within Bourdieu's concept of cultural capital and its reproduction, its conversion to other forms of capital, and the notion of habitus. I also investigate a few of Kasilag's compositions to determine how she expressed her idea of a Filipino sound, reflective of its modernized and nationalistic sensibilities.